Consumption of Fruitflow® lowers blood pressure in pre-hypertensive males: a randomised, placebo controlled, double blind, cross-over study. (19th May 2018) - Uddin, Main; Biswas, Dipankar; Ghosh, Abhik; O'Kennedy, Niamh; Duttaroy, Asim K.
Abstract: In order to investigate whether the angiotensin converting enzyme-inhibitory tomato extract Fruitflow ® would lower blood pressure after consumption, we conducted a randomised, double-blinded, placebo-controlled human intervention study, involving 12 pre-hypertensive people in a crossover design. Consuming a single dose of 150 mg Fruitflow ® resulted in a significant reduction in 24-hour average blood pressure as well as average wake-period and sleep-period SBP, compared to placebo. Other parameters related to blood pressure, such as 24-hour average mean arterial pressure, pulse pressure, heart rate, central aortic systolic pressure and radial augmentation index were also reduced. In addition, the platelet aggregation response to ADP, measured 24 hours after consuming Fruitflow ®, fell significantly compared to baseline, and compared to placebo. This pilot study clearly shows the beneficial effects of Fruitflow ® on two important cardiovascular risk factors, high blood pressure and platelet hyperactivity.